Principles of economics - Lipsey, Richard G. (Oxford University Press, 1999)
This edition has been rewritten to take account of the latest international developments and the core material revised to ensure students have the best possible account of both theory and practice of the subject. The book provides the student with a thorough grounding in all the theoretical components of a first course in economics, supported with world-wide case studies. Learning aids such as chapter summaries, topics for review, discussion questions and a glossary of economic terms all help to guide the student through the course, whilst a lively four-colour text design, and over three hundred annotated figures present information in a stimulating format. A range of ancillary products to accompany the text includes a test bank of revision questions, instructor's manual and set of overhead transparency masters